(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Water is an essential natural resource for the existence of all living organisms and metabolic processes in the world. Lakes have always been of great importance to mankind being the valuable natural resources. From the ancient times they have always been supplier of water for domestic, industrial & irrigation purposes. A lake also plays an important role of catalyst in the development of any city but unfortunately, the popularity of lakes often leads to its deterioration. Due to increasing urbanization, industrialization & other developmental activities, the capacity & quality of lake water is getting deteriorated. Therefore, the present study has been undertaken to assess the quality of lake water &to study its possible Environmental impacts.Considering these factors and necessity this paper took the review of the existing literature of the modeling processes and to evaluate the lake water quality status.